Improving Students’ Achievement in Learning Indonesian Through The Implementation of The Jigsaw Cooperative Method In year IX. F of MTSN 3 West Aceh - AH, Rozita Hasni (LUMBUNG AKSARA, 2022)
The purpose of this research was to improve the interest and learning outcomes of Year IX students who did not reach the passing grade in learning Indonesian through the implementation of the Jigsaw Cooperative Method. The researcher found that there was an inappropriate method in the learning process. The researcher involved colleagues to examine, observe, and find the solutions together.The problems to be studied in this action research were: a. Did the Jigsaw Cooperative Method affect students’ learning outcomes in Indonesian? b. How high was the mastery level of Indonesian subject matter with the application of the Jigsaw cooperative learning method? While the objectives of this study were: a. To reveal the effect of the jigsaw cooperative learning model on Indonesian learning outcomes. b. To know how far the understanding and mastery of Year IX.f students of MTsN 3 West Aceh in Indonesian subjects after the implementation of the jigsaw cooperative learning model. This study used three rounds of action research. Each round consisted of four stages: design, activity and observation, reflection, and revision. The target of this research was students of class IX.f of MTsN 3 West Aceh. The data obtained was in the form of formative test results, observation sheets of teaching and learning activities. Based on the results of the analysis, it was found that students’ achievement improved from cycle I to cycle III, that was, 60.71% in cycle I, 75.00% in cycle II, and 89.29% in cycle III. The conclusion of this study was that the Jigsaw cooperative learning model has a positive effect on the learning motivation of Year IX.f students of MTsN 3 West Aceh and this learning model can be used as an alternative in learning Indonesian